Farming Intensification and Environmental Justice in Northern Ireland - Gladkova, Ekaterina (2020)
Going for Growth, an industry-led strategy to expand the agri-food sector, was adopted by the Northern Irish government in 2013 in order to encourage farming intensification in Northern Ireland. This approach, however, threatens an already fragile natural environment and has already had detrimental consequences for human health and well-being. This article employs an environmental justice perspective to scrutinize farming intensification in a community affected by this phenomenon. Based on findings from semi-structured interviews with local residents, the article describes their exposure to environmental risks as a result of farming intensification. The uneven distribution of environmental burdens is also coupled with limited opportunities for the local residents to engage in environmental decision-making and to be recognized as active agents of change. The article concludes that farming intensification in Northern Ireland is marked by procedural environmental injustice and should be addressed by downscaling levels of production and reforming decision-making processes